Clinico-pathological and radiological correlation of CNS tumors along with role of Ki 67 proliferative index in grading Astrocytoma and Meningiomas - Boni, Lakshmi Saraswathi; Kondapalli, Mounika; Kotni, Venkata Swarajya Lakshmi; Botta, Venkata Satya Kartheek; Prasad, Uma; Atla, Bhagyalakshmi (International Journal of Research in Medical Sciences, 2019)
Background: CNS neoplasms are a heterogenous group contributing to <2% of all the malignant neoplasms. Imaging and histopathology play a great role in diagnosing these lesions. Aim of the study is to correlate radiological findings with that of histopathology and evaluate the role of Ki 67 proliferative index in various grades of Astrocytomas and Meningiomas Methods: This is an observational study for a period 2 years from July 2015 to June 2017 in Department of Pathology Andhra Medical College. The total number of specimens of CNS tumors received during this period were126. The specimens were routinely processed and stained with H&E. The tumors were classified based on WHO 2016 classification. In total 71 cases-45 cases of meningiomas and 26 cases of astrocytomas, the expression of Ki 67 labelling index was recorded in various grades of these tumors and results tabulated. Results: Among 126 cases, tumors predominantly encountered were of meningeal origin accounting to 45 cases (35.71%) followed by tumors of neuroepithelial origin 35 cases (27.78%). Tumors were seen in all age groups, but common was among 41-50 years of age group with metastatic tumors being seen in >60 year group. Tumors were more common in males with male: female ratio being 1.25:1. Ki 67 proliferative index increased as the grade of tumor increased in both astrocytomas and meningiomas. Conclusions: Grading of meningiomas and astrocytomas are very much essential with reference to prognosis and therapy. Histopathology plays a great role in grading these lesions but Ki 67 proliferative index adds as an adjunct and helps in confirmation and predicting the recurrence of these lesions.